Influence Of Air Exchange Effectiveness On Thermal Comfort In Malaysia - Daghigh, Roonak (2008)

(untitled)
Influence of air exchange rate and air exchange effectiveness on thermal comfort has not been investigated in the world at all and are, therefore, not well understood. The main objective of this research is to investigate effects of ventilation parameters on thermal comfort and assessing these influences through the variable windows-door opening arrangements. To determine the windows-door opening performance in terms of ventilation air flow rate 28 opening configurations have been considered. The combination of windows-door opening arrangements was carried out in office room. Thermal comfort field experiments and ventilation study were conducted in both naturally ventilated and air conditioned office. Age of air, Air exchange rate (ACH), Air exchange effectiveness (AEE), Predicted Mean Vote (PMV) and predicted Percentage of Dissatisfied (PPD) for each condition were calculated. Apart from common thermal comfort factors such as air dry bulb temperature, relative humidity,mean radiant temperature, air velocity, metabolic rate and thermal resistance, two new factors were considered, i.e., ACH and AEE. The subjective survey involved questions on the thermal environmental perception and indoor air quality for office occupants. The results yielded from subjective and objective approach were used to formulate a method for simulation of office buildings to include the effects of opening arrangements and ventilation parameters on thermal comfort. These results showed that for naturally ventilated and air conditioned office room twelve linear regression equations of PMV versus ACH and AEE can be derived. Through those yielded equations it has been determined that the Coefficient of Correlation (R2) obtained for PMV average, maximum and minimum versus ACH are 96.5, 93.9, 97.3% and 94.3, 89.9, 86.6%, respectively. The Coefficient of Correlation (R2) obtained for PMV average, maximum and minimum versus AEE are 74.9, 70.7, 76.9% and 88.7, 76.5, 86.7%, respectively for naturally and mechanically ventilated office room. P values (significance levels) for ANOVA test and t-test are less than 0.05, which means that the variation explained by these equations not due to chance and there are significant correlation between PMV and ACH and high correlation between PMV and AEE in naturally and mechanically ventilated office room. It has been observed that with increment in ACH in order to meet ASHRAE Standard 62 requirements, PMV values are closed to ISO 7730 comfort range, and by approaching the AEE to value of one, PMV values are again closed to ISO 7730 comfort range in naturally and mechanically ventilated office room. This study has shown that there are relationship between ACH, AEE and thermal comfort. Thermal comfort is to a great extent influenced by ACH and AEE which go beyond the six factors which have been taken into account in PMV modeling. It is believed that they have contributed in some positive ways to the higher level of thermal comfort.